The biochemical composition of young sturgeon reared with the KRT - Kairov, E.A.; Shaldaeva, R.E. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva; "Zvaigzne", 1968)
The biochemical analysis of three sturgeon species: of the North-Caspian (Russian) sturgeon Acipenser gueldenstaedti, the Baikal (Siberian) sturgeon Acipenser baeri and the Lena (Eastern Siberian) sturgeon Acipenser baeri stenorrhynchus was carried out. The results indicate that the usage of the artificial forage KRT as the main feed for rearing of the sturgeon fry for the release into the water bodies, allows to get viable juveniles of high physiological standard, fully fit for the life in the natural water bodies. Published Not Known